2020
DOI: 10.1101/2020.02.28.963280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redefining CD4 T cell residency: Helper T cells orchestrate protective humoral immunity in the lung

Abstract: Influenza is a severe and acute respiratory pathogen, and a significant cause for morbidity, particularly in young children and the elderly. Following influenza infection, clonally expanded T cells take up permanent residence in the lung where they are poised to rapidly respond to challenge infection. The non-circulating status of these tissue resident memory (TRM) cells makes them an attractive target for vaccination. While many studies have characterized CD8 TRM cells, less is known about the heterogeneity a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…We find that overall in CD4 CSF clusters, CD4 memory CSF.3 has the highest expression of genes related to all three signatures, followed by CD4 memory CSF.2, which had higher expression of all three signatures compared with CD4 clusters in the blood and CD4 memory CSF.1. This supports that, compared with the peripheral blood, the healthy CSF is enriched for CD4 T cells with T H 1 function, including a CD4 subtype with cytotoxic capacity, and that these cells may adapt to the tissue environment in ways similar to what has been described in other tissues (24,25,34).…”
Section: Phenotypic Continuum Of T Cell States Between the Blood And Csfsupporting
confidence: 78%
See 1 more Smart Citation
“…We find that overall in CD4 CSF clusters, CD4 memory CSF.3 has the highest expression of genes related to all three signatures, followed by CD4 memory CSF.2, which had higher expression of all three signatures compared with CD4 clusters in the blood and CD4 memory CSF.1. This supports that, compared with the peripheral blood, the healthy CSF is enriched for CD4 T cells with T H 1 function, including a CD4 subtype with cytotoxic capacity, and that these cells may adapt to the tissue environment in ways similar to what has been described in other tissues (24,25,34).…”
Section: Phenotypic Continuum Of T Cell States Between the Blood And Csfsupporting
confidence: 78%
“…The CD4 memory CSF.1 cluster was marked by expression of the subunits of the alpha 4 (ITGA4) beta 1 (ITGB1) integrin, which has been shown to be important for T cell entry into the CNS (1), KLRB1, and S1PR1 that promotes T cell egress from tissues (31). The other two CD4 clusters in the CSF (CD4 memory CSF.2 and CD4 memory CSF.3) have phenotypes similar to each other characterized by the chemokine receptor CXCR3 associated with T H 1 cells and CSF T cell trafficking (2,32) and markers that have been found in tissue-resident T cells and T cells residing within nonlymphoid tissues, including CCL5 (24,33,34), LGALS1 (24,25,34), PTGER2 (35), and CD69 (36). However, CD4 memory CSF.3 was also defined by the cytotoxicity-related genes GZMA, GZMK, GZMM, and CST7 (37), whereas CD4 memory CSF.2 was not.…”
Section: Phenotypic Continuum Of T Cell States Between the Blood And Csfmentioning
confidence: 99%
“…This differs from influenza, which elicits these features in addition to lung BRM cells (8,11). The tendency to be associated with areas of iBALT varies among the distinct populations of lung TRM cells in influenza-recovered mouse lungs (40). However, B cell studies in the context of influenza have not reported lung B cells outside of iBALT (40)(41)(42), and it is therefore unclear whether influenza-generated lung BRM cells reside only in these structures.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency to be associated with areas of iBALT varies among the distinct populations of lung TRM cells in influenza-recovered mouse lungs (40). However, B cell studies in the context of influenza have not reported lung B cells outside of iBALT (40)(41)(42), and it is therefore unclear whether influenza-generated lung BRM cells reside only in these structures. The current pneumococcus studies dissociate BRM cells from localization exclusively in iBALT and reveal that lung BRM cells can be components of histologically unremarkable lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, also the responsiveness of T cells to chemokines in barrier tissues (and the mode of their regulation) is critical for defining the retention of T RM cells in the tissue. Some members of the the regulator of G protein signaling (RGS) family, including RGS1, are consistently overexpressed in T RM cells from barrier tissues [65,[81][82][83], but also in tumorinfiltrating T cells [84,85]. These RGS family members enhance the GTPase activity of GTP-bound Gαi (also Gαq) and, thus, inhibit Gαi/αq-coupled receptor signaling [86,87].…”
Section: Retention Of T Rm Cells In the Intestinal Mucosamentioning
confidence: 99%